Electrolytic capacitor
Patent Information
- Application Number
- JP2023143099
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-14
AI Technical Summary
【0007】 本発明によれば、セパレータ中央部に電解液を多く保持するため、誘電体層の被膜修復効果が向上し初期容量を改善できるとともに、電解液が素子端部から蒸散しても素子中央部に保持される電解液を端部に供給可能なため、初期容量を維持することができる。
Smart Images

Figure 2025035814000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor. [Background technology]
[0002] As an electrolytic capacitor with a small size, large capacity, and low ESR (equivalent series resistance), an electrolytic capacitor including an anode foil with a dielectric layer, a conductive polymer layer with high electrical conductivity formed so as to cover at least a part of the dielectric layer, and an electrolyte capable of repairing the oxide film that is the dielectric layer of the anode is considered to be promising. As such an electrolytic capacitor, for example, a capacitor has been disclosed in which a capacitor element is impregnated with a solution containing undoped soluble polyaniline, a polyaniline layer is formed, and then a conductive polymer layer is formed (see, for example, Patent Document 1). Also, a capacitor using an electrolyte containing a glycerin compound and γ-butyrolactone has been disclosed (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-93417 A [Patent Document 2] JP 2016-82053 A Summary of the Invention [Problem to be solved by the invention]
[0004] Electrolytic capacitors used in automotive electrical equipment are used for long periods of time in high-temperature environments, and are therefore required to maintain their initial capacity more than ever before. Patent Document 1 provides an electrolytic capacitor with improved reliability by immersing a capacitor element in a polyaniline solution to form a polyaniline layer, and then forming a conductive polymer layer. Patent Document 2 provides an electrolytic capacitor with high reliability by using an electrolyte solution containing γ-butyrolactone and a glycerin compound such as glycerin. However, neither method meets the requirement for maintaining the initial capacity.
[0005] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide an electrolytic capacitor capable of maintaining its initial capacitance. [Means for solving the problem]
[0006] The electrolytic capacitor of the present invention comprises a capacitor element having an anode foil having an anodized coating on its surface, a cathode foil, and a separator inserted between the anode foil and the cathode foil, a conductive polymer impregnated in the capacitor element, and an electrolyte impregnated in the capacitor element, wherein a mass E2 per unit volume of the electrolyte impregnated in the center of the separator is greater than a mass E1 per unit volume of the electrolyte impregnated in the end portion of the separator. Effect of the Invention
[0007] According to the present invention, a large amount of electrolyte is retained in the central portion of the separator, thereby improving the coating repair effect of the dielectric layer and improving the initial capacity. Furthermore, even if the electrolyte evaporates from the ends of the element, the electrolyte retained in the central portion of the element can be supplied to the ends, thereby maintaining the initial capacity. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic diagram of an electrolytic capacitor according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a simplified diagram of a partial cross section of a capacitor element (before being impregnated with a conductive polymer) according to an embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view that shows a schematic diagram of a state in which the capacitor element according to the embodiment of the present invention is impregnated with a conductive polymer. [Figure 4] FIG. 4 is an image of the separator surface according to an embodiment of the present invention. [Diagram 5] FIG. 5 shows surface images of an anode foil and a cathode foil according to an embodiment of the present invention. [Figure 6] FIG. 6 is an image of the surface of a separator according to a comparative example. [Figure 7] FIG. 7 shows surface images of an anode foil and a cathode foil according to a comparative example. [Figure 8] FIG. 8 is a cross-sectional view that illustrates a schematic state of a conductive polymer layer of an electrolytic capacitor according to a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment will be described with reference to the drawings.
[0010] (Embodiments of the present invention) Fig. 1 is a schematic diagram of an electrolytic capacitor 1 according to an embodiment of the present invention. Fig. 2 is a simplified diagram of a partial cross section of a capacitor element 20 (before conductive polymer impregnation) according to an embodiment of the present invention. Fig. 3 is a cross section diagram showing a schematic state of the capacitor element 20 according to an embodiment of the present invention impregnated with a conductive polymer. The electrolytic capacitor 1 includes a metal case 10 that functions as an exterior body, a capacitor element 20 inserted in the metal case 10, and a sealing body 30. A cylindrical aluminum case with a bottom and an opening 11 at one end is used as the metal case 10. In this embodiment, the metal case 10 has a cylindrical shape as an example, but may have a rectangular cylindrical shape.
[0011] Capacitor element 20 includes a pair of electrode foils. The pair of electrode foils is an anode foil 21 and a cathode foil 22. Capacitor element 20 is a wound type in which a first separator 23a, an anode foil 21, a second separator 23b, and a cathode foil 22 are layered in this order and wound. The shape of capacitor element 20 approximately matches the inner shape of metal case 10. Thus, capacitor element 20 has a columnar shape. In this embodiment, the capacitor element 20 is of a wound type (approximately cylindrical) that can effectively utilize the short-circuit path effect in electron transfer, but it may also be of a stacked type capacitor element (approximately rectangular column) in which anode foil and cathode foil are stacked in sequence with a separator between them.
[0012] The anode foil 21 and the cathode foil 22 may be made of valve metals such as aluminum, tantalum, titanium, niobium, and alloys thereof, or evaporated foils. The anode foil 21 has an oxide film covering the entire surface. Therefore, the anode foil 21 is insulated from other members. The oxide film functions as a dielectric, and the capacitor element 20 functions as a capacitor. The surfaces of the anode foil 21 and the cathode foil 22 have porous portions 21a and 22a formed by etching or the like. The cathode foil 22 may have an inorganic layer or a carbon layer formed on the surface. In this case, a conductive polymer layer, which will be described later, is also formed on the surface on which the inorganic layer or the carbon layer is formed. An anode lead terminal 24a is connected to the anode foil 21. A cathode lead terminal 24b is connected to the cathode foil 22.
[0013] The sealing body 30 is made of a rubber sealing body having a pair of lead insertion holes 31a, 31b through which the anode lead terminal 24a and the cathode lead terminal 24b are inserted. The sealing body 30 is fitted into the opening 11 of the metal case 10, and is tightly and airtightly attached by a horizontal squeeze groove 12 formed along the outer periphery of the opening 11 by a crimping piece or the like. For example, butyl rubber or the like having a small swelling rate with respect to the solvent of the electrolyte solution described below is used for the sealing body 30. This makes it possible to reduce the influence of impurities extracted by ethylene glycol on the capacitor characteristics when the electrolyte solution contains ethylene glycol. Specifically, it is preferable to use butyl rubber having a swelling rate of less than 0.4% by mass even when immersed in an ethylene glycol solvent at 125° C. for 2000 hours or more, and a swelling rate of less than 2% by mass even when similarly immersed in a γ-butyrolactone solvent for 2000 hours or more.
[0014] The capacitor element 20 is impregnated with a conductive polymer. Examples of the conductive polymer include polythiophene, polypyrrole, polyaniline, polyacetylene, polyfuran, polyacetylene, polyparaphenylene, polyparaphenylenevinylene, polyacene, and polythiophenevinylene. The conductive polymers described above may be used alone or in combination of two or more. The conductive polymer may be a polymer containing at least 50% by mass of a basic monomer constituting the conductive polymer, such as thiophene or pyrrole, preferably 70% by mass or more, and more preferably 90% by mass. As the conductive polymer, poly(3,4-ethylenedioxythiophene) containing 3,4-ethylenedioxythiophene as a monomer unit can be preferably used.
[0015] The conductive polymer preferably contains a dopant. Examples of the dopant include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacryl sulfonic acid, polymethacryl sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. The above-mentioned dopants may be used alone or in combination of two or more.
[0016] The first separator 23a and the second separator 23b may be made of the same material or different materials. For example, glass fiber, cellulose, rayon, polyethylene terephthalate, vinylon, aliphatic polyamide, and aromatic polyamide can be used for the first separator 23a and the second separator 23b. A blend of cellulose, rayon, and glass fiber can be preferably used for the first separator 23a and the second separator 23b.
[0017] The capacitor element 20 is impregnated with an electrolytic solution. The electrolytic solution is not limited as long as it can be used in an electrolytic capacitor, and either a γ-butyl lactone-based non-aqueous electrolytic solution or an ethylene glycol-based aqueous electrolytic solution can be used. Examples of solute components contained in the electrolytic solution include aliphatic carboxylic acids such as adipic acid, aromatic carboxylic acids such as phthalic acid, ammonia, amines such as triethylamine, and amidines such as tetramethylimidazolinium.
[0018] 2 and 3, the anode foil 21 and the cathode foil 22 are structured to face each other with an insulating first separator 23a and a second separator 23b interposed therebetween, and the first separator 23a and the second separator 23b prevent a short circuit between the anode foil 21 and the cathode foil 22. In the electrolytic capacitor 1, the first separator 23a and the second separator 23b separating the anode foil 21 and the cathode foil 22 are impregnated with a conductive polymer dispersion liquid, and the dispersion medium is dried to form a conductive polymer layer on the anode foil 21, the cathode foil 22, and the porous portion 21a and surface of the separator. This allows a low ESR to be achieved.
[0019] As shown in FIG. 3, in the electrolytic capacitor 1 according to the embodiment of the present invention, a band-shaped agglomerate 25 made of a conductive polymer is formed at the end of the capacitor element 20. In this specification, the end 20a of the capacitor element 20 means the end in the direction (width direction) perpendicular to the winding direction of the capacitor element 20. The end 20a of the capacitor element 20 is within each 15% of the length in the direction perpendicular to the winding direction. The central portion 20b of the capacitor element 20 is the central portion in the length direction perpendicular to the winding direction, and is within 70% of the length in the direction perpendicular to the winding direction. In the case where the capacitor element is a laminated type, the end of the capacitor element is within a range of 15% of the length from each rectangular end face, and the central portion is within a range of 70% excluding the end.
[0020] In the electrolytic capacitor 1, the conductive polymer band-shaped agglomerates 25 are formed at the end 20a of the capacitor element 20, so that the conductive polymer is impregnated into the porous portion at the end 20a of the capacitor element 20, and the amount of the conductive polymer impregnated into the porous portion at the center 20b is reduced. Therefore, the ratio (S2) of the voids at the center of the first separator 23a and the second separator 23b is greater than the ratio (S1) of the voids at the end. The volume of the voids increases from the end to the center of the first separator 23a and the second separator 23b. The impregnation amount and porosity of the conductive polymer of the first separator 23a and the second separator 23b can be calculated from the change in mass before and after the impregnation with the conductive polymer, which will be described later, and can also be measured by SEM-EDS of a cut surface perpendicular to the winding direction of the separator.
[0021] When the band-shaped agglomerates 25 made of conductive polymer are formed mainly at the end 20a of the capacitor element 20, the band-shaped agglomerates 25 made of conductive polymer can be seen from the end of the capacitor element 20. The width of the band-shaped agglomerates 25 made of conductive polymer formed on the first separator 23a and the second separator 23b varies depending on the size of the capacitor element 20, but is preferably 0.1 to 3 mm. By forming the band-shaped agglomerates 25 made of conductive polymer over the above width at the end of the first separator 23a and the second separator 23b, the proportion of voids in the center is relatively higher than that at the end, and the amount of electrolyte that can be retained is increased.
[0022] The electrolyte is held in the voids of the first separator 23a and the second separator 23b. Since the ratio S2 (average) of the voids in the centers of the first separator 23a and the second separator 23b is greater than the ratio S1 (average) of the voids in the ends, the mass E2 (average) per unit volume of the electrolyte impregnated in the centers of the first separator 23a and the second separator 23b is greater than the mass E1 (average) per unit volume of the electrolyte impregnated in the ends.
[0023] In the capacitor element 20, the central portion 20b holds a large amount of electrolyte, which improves the effect of repairing the coating of the aluminum dielectric layer at the center of the anode foil, reduces the number of defective coating portions, and improves the initial characteristics. In addition, because the central portion 20b holds a large amount of electrolyte, even if the electrolyte evaporates from the ends of the capacitor element 20, it is possible to supply electrolyte from the central portion 20b, and an electrolytic capacitor that maintains the initial characteristics for a long period of time can be provided.
[0024] The liquid volume ratio E2 / E1 of the mass E1 (average) per unit volume of the electrolyte impregnated into the ends of the first separator 23a and the second separator 23b to the mass E2 (average) per unit volume of the electrolyte impregnated into the central parts of the first separator 23a and the second separator 23b is preferably 1.05 or more, more preferably 1.10 or more, even more preferably 1.20 or more, and particularly preferably 1.67 or more.
[0025] FIG. 4 is an image of the surface of a separator according to an embodiment of the present invention. FIG. 5 is an image of the surface of an anode foil (FIG. 5(A)) and a cathode foil (FIG. 5(B)) according to an embodiment of the present invention. As shown in FIG. 4, strip-shaped agglomerates 25 (black parts) made of conductive molecules are mainly formed at the ends of the separator 23, and there is a white part in the center where strip-shaped agglomerates 25 made of conductive polymer are not formed. The white part in the center is an area that can hold more electrolyte because it is less impregnated with conductive polymer, and strip-shaped agglomerates 25 made of conductive polymer are formed at the ends to block it, so the center becomes a dam-like state where electrolyte is accumulated. In addition, as shown in FIGS. 5(A) and (B), respectively, it can be seen that the anode foil 21 and the cathode foil 22 are also impregnated with a lot of black parts of conductive polymer at the ends and have less conductive polymer in the center.
[0026] FIG. 6 is an image of the separator surface according to the comparative example. FIG. 7 is an image of the surface of the anode foil (FIG. 7(A)) and the cathode foil (FIG. 7(B)) according to the comparative example. As shown in FIG. 6, in the separator 23 of the capacitor element according to the comparative example, the conductive polymer is almost uniformly impregnated into the separator 23. Since there is little white part (void) in the center where the conductive polymer is not impregnated, and no band-shaped agglomeration of the conductive polymer is formed at the end, the dam effect disappears and the amount of electrolyte held in the void part (white part) in the center becomes small. If the amount of electrolyte held is small, the coating repair effect is reduced and the initial characteristics cannot be maintained. Furthermore, if the electrolyte evaporates from the end of the capacitor element, there is no surplus electrolyte that can replenish the evaporated electrolyte, so the electrode connection disappears from the evaporated part, causing deterioration of characteristics. Also, as shown in FIGS. 7(A) and 7(B), respectively, it can be seen that the conductive polymer is also almost uniformly formed in the anode foil 21 and the cathode foil 22.
[0027] Fig. 8 is a cross-sectional view showing a schematic diagram of the impregnation state of the conductive polymer in the electrolytic capacitor according to the comparative example. In Fig. 8, the conductive polymer dispersion liquid is impregnated from the lower side of the page, and the amount of impregnated conductive polymer gradually decreases from the end of the lower side of the capacitor element 20 to the center and the end of the upper side. When the conductive polymer is formed as shown in Fig. 8, there is no portion that can hold a large amount of electrolyte, so the coating repair effect is reduced, the initial characteristics are not improved, and there is no electrolyte to make up for the shortage that has evaporated from the end, which causes the characteristics to deteriorate accordingly.
[0028] A method for forming band-shaped agglomerates 25 made of conductive polymer in electrolytic capacitor 1 according to an embodiment of the present invention will be described. In order to form band-shaped agglomerates 25 made of conductive polymer mainly at end portion 20a of capacitor element 20, it is important to adjust the conductive polymer in the conductive polymer dispersion with which capacitor element 20 is impregnated, the viscosity of the conductive polymer dispersion, and to control the impregnation conditions.
[0029] The conductive polymer dispersion liquid to be impregnated into the capacitor element preferably has a conductive polymer mass ratio of 0.5 mass% or more, more preferably 1 mass% or more, and even more preferably 1.5 mass% or more. Also, the conductive polymer dispersion liquid to be impregnated into the capacitor element preferably has a conductive polymer mass ratio of 2.2 mass% or less, more preferably 2.1 mass% or less, and even more preferably 2.0 mass% or less. The viscosity of the conductive polymer dispersion is preferably 10 mPa·s or more, and more preferably 15 mPa·s or more, at 20° C. The viscosity of the conductive polymer dispersion is preferably 30 mPa·s or less, and more preferably 25 mPa·s or more, at 20° C.
[0030] The impregnation of the capacitor element with the conductive polymer dispersion liquid is carried out by first reducing the pressure inside a box in which the conductive polymer dispersion liquid and the capacitor element are placed to remove the air from inside the capacitor element, and then immersing the capacitor element in the conductive polymer dispersion liquid. The impregnation of the capacitor element with the conductive polymer is carried out under reduced pressure of -100 kPa or more and -81 kPa or less. The impregnation time varies depending on the pressure atmosphere, but it is preferable to carry out the impregnation for 500 seconds or more and 1000 seconds or less. The impregnation of the capacitor element with the conductive polymer is preferably carried out under reduced pressure of -100 kPa or more and less than -91 kPa. EXAMPLES
[0031] The present invention will now be described in more detail with reference to examples, in which the methods for measuring the properties are as follows.
[0032] <Porosity of the separator and amount of electrolyte impregnated> In each example and comparative example, the capacitor element was impregnated with a conductive polymer dispersion and dried at 150°C for 60 minutes to remove the solvent, and then the capacitor element was disassembled and the separator was cut into ends (15% from the end in the length direction) and a center portion (70% at the center), and the mass of each portion was measured. Similarly, a separator not impregnated with the conductive polymer was used as a reference, cut into ends and a center portion, and its mass was measured. The mass of the reference was subtracted from the mass of the ends and center portion of the separator in each example and comparative example to calculate the conductive polymer formed in each portion (conductive polymer per unit area). The density (1 g / cm) of the conductive polymer 3 ) and the porosity after the conductive polymer layer was formed was calculated from the initial void volume of the separator. The amount of the electrolyte was calculated assuming that the electrolyte was impregnated into the calculated voids in the separator.
[0033] <Capacitance> The electrolytic capacitors of each Example and Comparative Example were measured for capacitance (initial capacitance) (μF) at a frequency of 120 Hz using a four-terminal LCR meter. After that, each electrolytic capacitor was left for 500 hours in a 125°C environment with various rated voltages applied, and the electrolytic capacitance (post-test capacitance) (μF) was measured.
[0034] <Visual confirmation of band-like agglomerates made of conductive polymer> When the electrolytic capacitors of each of the examples and comparative examples were observed from the end direction, it was confirmed whether or not the conductive polymer was visible. <Width of the band-shaped agglomerates made of conductive polymer> In each example and each comparative example, the capacitor element was impregnated with the conductive polymer dispersion and dried at 150°C for 60 minutes to remove the solvent, and then the capacitor element was disassembled and the width of the band-like agglomerate of conductive polymer formed at the edge of the separator was measured. For each sample, measurements were taken at 5 locations on each side, for a total of 10 locations, and the average value was calculated.
[0035] Example 1 In Example 1, a wound electrolytic capacitor (diameter 8.0 mm×length 10.0 mm) was produced with a rated voltage of 63 V and a rated capacitance of 33 μF. A specific method for producing the electrolytic capacitor will be described below. (Making of the roll) An anode lead terminal was connected to the aluminum anode foil on which an oxide film had been formed. A cathode lead terminal was connected to an aluminum cathode foil that had a conductor layer on its end surface and had been pretreated to improve wettability. The first separator, cathode foil, second separator, and anode foil were then laminated in that order, and the lead terminal was rolled up while being wrapped around the foil, and the outer surface was fixed with a stopper tape to produce a wound body. The wound body was then immersed in an ammonium phosphate aqueous solution, and the anode foil was subjected to another chemical conversion treatment at 85°C while a voltage was applied to the anode foil, forming a dielectric layer mainly on the end surface of the anode foil.
[0036] (Fabrication of capacitor elements) The wound body was immersed in a conductive polymer dispersion liquid contained in a specified container in a reduced pressure atmosphere (-81 kPa), and impregnation with the conductive polymer dispersion liquid was performed under the conditions of a vacuum impregnation time of 500 seconds and an atmospheric exposure time of 72 seconds. Next, the wound body impregnated with the conductive polymer was dried in a drying furnace at 150°C for 60 minutes to impregnate the capacitor element with the conductive polymer. (Electrolyte Impregnation) The capacitor element was impregnated with an electrolyte for 30 seconds in a reduced pressure atmosphere (-93kPa). The electrolyte used was Teica's commercially available ESE2. (Sealing of capacitor elements) The capacitor element impregnated with the electrolytic solution was sealed in a metal case 10 to complete an electrolytic capacitor. After that, an aging treatment was performed at 85° C. for 1 hour while applying a rated voltage. The initial capacitance and the post-test capacitance of the produced electrolytic capacitor were measured. The results are shown in Table 1.
[0037] Example 2 An electrolytic capacitor was produced in the same manner as in Example 1, except that the impregnation conditions with the conductive polymer dispersion were a reduced pressure atmosphere (-93 kPa) and the impregnation time was 700 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 1. Example 3 An electrolytic capacitor was produced in the same manner as in Example 1, except that the impregnation condition with the conductive polymer dispersion was set to an impregnation time of 700 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 1.
[0038] Example 4 An electrolytic capacitor was produced in the same manner as in Example 1, except that the impregnation conditions with the conductive polymer dispersion were a reduced pressure atmosphere (-93 kPa) and the impregnation time was 900 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 1. Example 5 An electrolytic capacitor was produced in the same manner as in Example 1, except that the impregnation condition with the conductive polymer dispersion was changed to an impregnation time of 900 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 1. Example 6 In Example 6, a wound electrolytic capacitor (diameter 12.5 mm × length 16.5 mm) with a rated voltage of 25 V and a rated capacitance of 1000 μF was produced under the same conditions as in Example 1, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 2.
[0039] Example 7 An electrolytic capacitor was produced in the same manner as in Example 6, except that the impregnation conditions with the conductive polymer dispersion were a reduced pressure atmosphere (-93 kPa) and the impregnation time was 700 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 2. Example 8 An electrolytic capacitor was produced in the same manner as in Example 6, except that the impregnation condition with the conductive polymer dispersion was set to an impregnation time of 700 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 2. Example 9 An electrolytic capacitor was produced in the same manner as in Example 6, except that the impregnation conditions with the conductive polymer dispersion were a reduced pressure atmosphere (-93 kPa) and the impregnation time was 900 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 2.
[0040] Example 10 An electrolytic capacitor was produced in the same manner as in Example 6, except that the impregnation condition with the conductive polymer dispersion was changed to an impregnation time of 900 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 2. Comparative Example 1 An electrolytic capacitor was produced in the same manner as in Example 1, except that the impregnation conditions with the conductive polymer dispersion were a reduced pressure atmosphere (-93 kPa) and the impregnation time was 300 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 1. Comparative Example 2 An electrolytic capacitor was produced in the same manner as in Example 6, except that the impregnation conditions for the conductive polymer dispersion were a reduced pressure atmosphere (-93 kPa) and the impregnation time was 300 seconds, and the initial capacitance and the post-test capacitance were measured. The results are shown in Table 2.
[0041] [Table 1]
[0042] [Table 2]
[0043] It was confirmed that in Comparative Example 1, the initial capacity was low compared with Examples 1 to 5, and the capacity retention rate after standing for 500 hours was also low. It was confirmed that in Comparative Example 2, the initial characteristics were poorer than those in Examples 6 to 10, and the capacity retention rate after standing for 500 hours was also low. It is believed that the amount of electrolyte held in the center of the separator in the electrolytic capacitors of Comparative Examples 1 and 2 was small, which resulted in insufficient film repair and reduced initial capacity. In addition, electrolyte evaporated from the ends of the capacitor during testing in a 125°C environment, but there was no electrolyte to compensate for this, and the contact area with the electrode foil for capacity development decreased, which is believed to have resulted in a low capacity retention rate. In addition, the products after the test of each Example and Comparative Example were disassembled to confirm the amount of electrolyte held by the separator. In Examples 1 to 10, the amount of electrolyte in the center decreased, while the decrease in the amount of electrolyte at the edge was slight. This is because the liquid evaporated from the edge, and in Examples 1 to 10, since electrolyte was supplied from the center, the amount of electrolyte in the center decreased easily, while the amount of electrolyte at the edge was maintained. In contrast, in Comparative Examples 1 and 2, the amount of electrolyte at the edge decreased significantly. This is because, since there was no supply of electrolyte in Comparative Examples 1 and 2, the evaporation of electrolyte from the edge was noticeable. [Industrial Applicability]
[0044] The electrolytic capacitor according to the present embodiment has excellent initial characteristics and can maintain the initial characteristics even after long-term use, and therefore can be suitably used as an electrolytic capacitor for vehicles. [Explanation of symbols]
[0045] 1. Electrolytic capacitor 10 Metal case 11 Opening 12 Horizontal squeeze groove 20 Capacitor element 21 Anode foil 22 Cathode foil 22a Porous part 23a First separator 23b Second separator 24a Anode lead terminal 24b Cathode lead terminal 25 Conductive polymer strips 30 Sealing body 31a, 31b Lead insertion hole
Claims
1. a capacitor element including an anode foil having an anodized coating on a surface thereof, a cathode foil, and a separator inserted between the anode foil and the cathode foil; A conductive polymer impregnated in the capacitor element; an electrolyte impregnated in the capacitor element; an electrolytic capacitor, characterized in that a mass E2 per unit volume of the electrolyte impregnated in the center portion of the separator is greater than a mass E1 per unit volume of the electrolyte impregnated in the end portion of the separator;
2. 2. The electrolytic capacitor according to claim 1, wherein a band-shaped agglomerate made of the conductive polymer is formed at an end of the capacitor element.
3. 3. The electrolytic capacitor according to claim 1, wherein the width of the band-like agglomerate is 0.1 to 3.0 mm.
4. 3. The electrolytic capacitor according to claim 1, wherein the separator and the anode foil, and / or the separator and the cathode foil are bonded together with the conductive polymer.
5. 3. The electrolytic capacitor according to claim 1, wherein E2 / E1 is 1.05 or more.
6. 3. The electrolytic capacitor according to claim 1, wherein E2 / E1 is 1.10 or more.
7. 3. The electrolytic capacitor according to claim 1, wherein E2 / E1 is 1.20 or more.
8. 3. The electrolytic capacitor according to claim 1, wherein E2 / E1 is 1.67 or more.
9. 3. The electrolytic capacitor according to claim 1, wherein the capacitor element is a wound type.
10. 3. The electrolytic capacitor according to claim 1, wherein the capacitor element is a laminated type.
11. a capacitor element including an anode foil having an anodized coating on a surface thereof, a cathode foil, and a separator inserted between the anode foil and the cathode foil; A conductive polymer impregnated in the capacitor element; an electrolyte impregnated in the capacitor element; An electrolytic capacitor, wherein a ratio S2 of voids in a center portion of the separator is greater than a ratio S1 of voids in an end portion of the separator.
12. 12. The electrolytic capacitor according to claim 11, wherein the separator has an increased ratio of voids from the ends to the center.
Citation Information
Patent Citations
Solid electrolytic capacitor and method for manufacturing the same
JP2014093417A
Electrolytic capacitor
JP2016082053A